Virtual environments in mathematics learning (Agroindustria, Sociedad y Ambiente, 2016)
Observations of a Mathematical teacher on what happens during his labor may be assumed as part of his attributions or responsibilities. In that way, using a subjective criterion inscribed in the qualitative paradigm, in this study assumes the responsibility of presenting some considerations for the use of virtual environments in the learning of Mathematics for the Agronomy Engineering program in the Decanato de Agronomía de la Universidad Centroccidental “Lisandro Alvarado” (UCLA). The considerations in this essay, which exposed observed a surrounding reality, are the result of the hermeneutics of the author and his cultural capital, coordinated with other documentary research. Finally, it was concluded: benefits with the implementation of a virtual classroom for the course are relevant, urgent and necessary to help improve the learning of mathematics.Key words: Virtual environments, Mathematics learning
Keywords: Virtual environments, Mathematics learning